Meaningful hybrid e-training model for web-based computer education - Din, Rosseni; Kamarul Zaman, Muhammad Faisal; Zakaria, Mohamad Shanudin; Mastor, Khairul Anwar; Nordin, Mohamad Sahari; Abu Kassim, Noor Lide; Tunku Ahmad, Tunku Badariah; Ariffin, Siti Rahayah; Ishak, Noriah; Abdul Karim, Aidah; Abd Razak, Norizan (2010)
The main purpose of this study was to develop a model for meaningful hybrid e-training. Data collected from 213 ICT trainers were tested with confirmatory factor analysis using AMOS 7.0 to obtain two best-fit measurement models for the two latent variables. Overall reliability using Alpha-Cronbach test, items and persons reliability using the Rasch Model and content validation by experts suggested that the questionnaire is reliable and valid to measure a meaningful hybrid e-training program. The results showed that there is a positive strong relationship between hybrid e-training and meaningful e training. In brief the study showed a substantial effect of hybrid e-training towards achieving meaningful learning. In conclusion, the study suggested that, future training regarding the use of hybrid e-training should include all five components of a meaningful hybrid e-training instead of merely focusing on content.